Постмодерні форми політичного спротиву (на прикладі подій в Україні періоду кінця 2013-2014 років) - Natalia Khоmа (Facta Simonidis)
The dynamics of changing forms of social protest as well as new, postmodern forms of political action at the example of Revolution of Dignity of 2013-2014 and Ukraine-Russia military confrontation in 2014 have been analysed in this article. It has been proved that modern ways of expressing protest differ from the old ones in the use of ironic slogans, performance, creativity and non-violent actions. Revolutionary war space is represented as the accumulation of many genres (photos, graffiti, political posters, installations, sculptures, cartoons, etc.). It has been proved that political action in the postmodern reality is provocative having at its base a game, ritual, and symbolism. The perception of political events through the prism of entertainment has been emphasised.